Theoretical and methodological foundations for forensic commodity examination of garment products - Ya. O. Kulyk; Ye. M. Sobakar (Bulletin of Kharkiv National University of Internal Affairs)
The examination of garment products is a popular type of forensic commodity expertise in proceedings related to the protection of the interests of Ukrainian producers, business entities in the sale and rental of garment products, as well as the investigation of offences related to export and import operations.